2017
DOI: 10.1136/bmjgh-2016-000120
|View full text |Cite
|
Sign up to set email alerts
|

Are national policies on global health in fact national policies on global health governance? A comparison of policy designs from Norway and Switzerland

Abstract: BackgroundSince the signing of the Oslo Ministerial Declaration in 2007, the idea that foreign policy formulation should include health considerations has gained traction on the United Nations agenda as evidenced by annual General Assembly resolutions on global health and foreign policy. The adoption of national policies on global health (NPGH) is one way that some member states integrate health and foreign policymaking. This paper explores what these policies intend to do and how countries plan to do it.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…A multiple comparative case study of policy arenas prior to the adoption of NPGH in Norway and in Switzerland in 2012 was designed to answer this question, applying most similar systems design criteria for case selection (Jones et al 2017b). Informed consent was obtained from all participants in accordance with ethical guidelines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A multiple comparative case study of policy arenas prior to the adoption of NPGH in Norway and in Switzerland in 2012 was designed to answer this question, applying most similar systems design criteria for case selection (Jones et al 2017b). Informed consent was obtained from all participants in accordance with ethical guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, there is nascent knowledge about policy processes to develop such documents (Gagnon and Labonte 2013;Aluttis et al 2015). A comparison of the NPGH documents adopted in Norway and Switzerland showed that these policies target actors in the GHG system (Jones et al 2017b). NPGH arenas are multisectoral governing arrangements wherein actors from health, development, and foreign affairs sectors interact in policy action situations to make decisions about the government's work in global health and its governance (Jones et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…In a related concept, Kickbusch and Cassar Szabo (2014) suggested that governance in global health can be analyzed along three political spaces ‐ global health governance, global governance for health and governance for global health – with the latter referring to relevant institutions and mechanisms established at the national and regional level such as national global health strategies and regional strategies for global health. While global health implications of some of the national strategies (Jones et al, 2017) and regional initiatives such as the Belt and Road (Tang et al, 2017) have further been discussed in some depth, contributions of regional integration organizations and processes to this governance space remain, with the exception of the European Union (Emmerling and Heydemann, 2013; Steurs et al, 2018), largely unexplored.…”
Section: How Regional Integration Processes Contribute To Global Health?mentioning
confidence: 99%
“…The method we chose is to review published and gray literature, including legislation, policies, and government reports for each state under study, and related policy studies that might shed light on the implementation of such policy. Policy document analysis is a widely accepted method for tracking policy implementation (see e.g., Lavoie et al, 2013;Jones et al, 2017;Munthe-Kaas et al, 2019;Steinmann et al, 2020). We searched for documents publicly available online.…”
Section: Introductionmentioning
confidence: 99%